High‐Resolution Spin‐on‐Patterning of Perovskite Thin Films for a Multiplexed Image Sensor Array - Lee, Woongchan; Lee, Jongha; Yun, Huiwon; Kim, Joonsoo; Park, Jinhong; Choi, Changsoon; Kim, Dong Chan; Seo, Hyunseon; Lee, Hakyong; Yu, Ji Woong; Lee, Won Bo; Kim, Dae‐Hyeong (Advanced materials (Weinheim), 2017)
Inorganic–organic hybrid perovskite thin films have attracted significant attention as an alternative to silicon in photon‐absorbing devices mainly because of their superb optoelectronic properties. However, high‐definition patterning of perovskite thin films, which is important for fabrication of the image sensor array, is hardly accomplished owing to their extreme instability in general photolithographic solvents. Here, a novel patterning process for perovskite thin films is described: the high‐resolution spin‐on‐patterning (SoP) process. This fast and facile process is compatible with a variety of spin‐coated perovskite materials and perovskite deposition techniques. The SoP process is successfully applied to develop a high‐performance, ultrathin, and deformable perovskite‐on‐silicon multiplexed image sensor array, paving the road toward next‐generation image sensor arrays. A high‐resolution, high‐definition patterning method of perovskite thin films is reported. The patterning method (spin‐on‐patterning) is based on wetting/dewetting behavior of perovskite precursor solution during the spin‐coating process. This fast and facile process is compatible with various solution‐processing perovskite deposition techniques. By using this method, a high‐performance, ultrathin, and deformable perovskite‐on‐silicon multiplexed image sensor array is successfully achieved.